Child Head Circumference and Placental MFSD2a Expression Are Associated to the Level of MFSD2a in Maternal Blood During Pregnancy - Sánchez-Campillo, María; Ruiz-Palacios, María; Ruiz-Alcaraz, Antonio J.; Prieto-Sánchez, María Teresa; Blanco-Carnero, José Eliseo; Zornoza, Matilde; Ruiz-Pastor, María José; Demmelmair, Hans; Sánchez-Solís, Manuel; Koletzko, Berthold; Larqué, Elvira (Frontiers in Endocrinology, 2020)
Gestational diabetes mellitus (GDM) is a world-wide health challenge, which prevalence is expected to increase in parallel to the epidemic of obesity. Children born from GDM mothers have lower levels of docosahexaenoic acid (DHA) in cord blood, which might influence their neurodevelopment. Recently, the membrane transporter Major Family Super Domain 2a (MFSD2a) was associated with the selective transportation of DHA as lysophospholipids. The expression of the DHA membrane transporter MFSD2a is lower in GDM placentas, which could affect materno-fetal DHA transport. Humans with homozygous inactivating mutations in the MFSD2a gene present severe microcephaly and intellectual impairments. Herein, we intended to identify early blood biomarkers that may be of use during pregnancy to monitor the offspring development and the adequate nutritional interventions, such as nutritional supplementation, that may be selected to improve it. We evaluated MFSD2a expression in maternal blood at the third trimester of pregnancy, and its potential relationship with the expression of placental MFSD2a at delivery and child outcomes. Three groups of pregnant women were recruited: 25 controls, 23 GDM with dietary treatment, and 20 GDM with insulin treatment. Maternal and neonatal anthropometric and biochemical parameters were evaluated. MFSD2a was analyzed in placenta, blood and serum. MFSD2a protein expression in maternal blood was significantly lower in GDM groups and correlated with placental MFSD2a and Z-score neonatal head circumference during the first 6 months of life. The cord/maternal serum ratio of DHA, a solid indicator of materno-fetal DHA transport, was reduced in GDM groups and correlated with MFSD2a in maternal blood at the third trimester and in placenta at delivery. This indicates that altered MFSD2a levels in maternal blood during pregnancy might influence placental nutrient transport and fetal neurodevelopment. Furthermore, MFSD2a levels in maternal blood on the third trimester were inversely correlated to DHA in maternal serum lyso-PL. Thus, the level of MFSD2a in maternal blood could be used as a potential biomarker for the early detection of disturbances of MFSD2a expression during pregnancy and the subsequent consequences for the neurodevelopment of the child, as well as it may help to choose the optimal treatment approach for the affected subjects.